Job Satisfaction among Nursing Faculties of Chitwan District - Baral, Rojina; Bhatta, Rabina (Journal of College of Medical Sciences-Nepal, 2018)
Background: A healthier and harmonious working environment, ample of opportunity to grab in, considerable payable amount, a sound professional growth and many others are the major backbone for a satisfaction in the work. Nursing is a profession who has a long working hours, plenty of paper work, and a lot of pressure to make a naive practice in a real environment. Thus, this study focuses on job satisfaction among nursing faculties. Material and methods: A cross-sectional analytical study was conducted among 62 nursing faculties involved in teaching graduate nursing students. All the nursing faculties who are involved in teaching graduate nursing students were included in the study. Sample were collected from all five nursing college of chitwan district regulating graduate nursing program. Census method was used to collect the data. Job satisfaction survey was used to collect the data. The data gathered was analyzed using both descriptive and inferential statistics in SPSS software. Result: Among total of 62 participants, more than three fourth 79% of the participants were ambivalent (neither satisfied nor dissatisfied) whereas, 21% were dissatisfied in their jobs. Also, age (p=0.003)/ among all the socio demographic variable, internet facility (p=0.044) and increment in grade system (p=0.004) among the variable regarding organizational climate was found to be statistically significant with the job satisfaction. Conclusion: A healthier working environment with certain aspects for the personal and professional growth is vital to improve the job satisfaction thus empowering the nursing faculties for their best performances. Keywords: chitwan; nursing; satisfaction.